Association Between Head Computed Tomography Scan Images and Electroencephalogram with Outcome In Post Stroke Seizure Patients - Harefa, Armellia Solida; Cut Aria, Arina; Aida, Fithrie (Talenta Universitas Sumatera Utara, 2025)
Background: Seizures that occur after a stroke and have no previous history of epilepsy are referred to as post stroke seizures (PSS). Post stroke seizure increases patient mortality, disability at hospital discharge, as well as prolongation of hospital stay. Patients with post stroke seizure show poor functional outcome (mRS >2). Objective: To determine the association between head CT scan images and electroencephalogram (EEG) with outcomes in post-stroke seizure patients at Adam Malik Hospital Medan. Methods: This study is an observational analytic study with prospective cohort research methods with primary data sources obtained consecutively from all PSS patients who were hospitalized at Adam Malik Hospital Medan and had undergone head CT scan and EEG examinations. The outcome of PSS patients was assessed by mRS score on day 14 since seizure. Results: There were 24 research subjects who met the inclusion and exclusion criteria aged between 18-74 years and consisted of 18 male subjects and 6 female subjects. There is a association between head CT scan images and clinical outcomes of post-stroke seizure patients based on the results of the chi square test with p value = 0.041 (<0.05) for lesion location and p = 0.018 (<0.05) for lesion size. There is a association between EEG and clinical outcomes of post-stroke seizure patients based on the results of the Chi Square test with p value = 0.001 (<0.05). Conclusion: There is a significant association between head CT scan images and EEG images and patient outcomes. Keyword: Post Stroke Seizure, Head CT Scan, EEG, outcome, mRS